INTERPRETASI SIMBOLIK APAY SEBAGAI PROSES INISIASI MASYARAKAT TUBABA MELALUI PERTUNJUKAN TIKEW: CIRCLE OF LIFE - Zefanya, Arsya Putri; Isa Ansari, Isa Ansari (Universitas Negeri Surabaya, 2025)
Tikew is one of plants that gorws on swampy areas, in Tulang Bawang Barat, Tiyuh Gedung Ratu. One of the products made form Tikew is Apay, which is part of the local wisdom of the Tubaba community and is used in daily life. The implementation of Apay as an initiation maker of daily life in the Tubaba community is directly related to the philosophy they call